Gastric Carcinoma in Young Patients and Its Clinicopathological Characteristics and Prognosis - Bhushan Sandeep; Xin Huang; Yuan Li; Long Mao; Ke Gao; Zongwei Xiao (Gastroenterology Research and Practice)
Background. Gastric cancer is usually an age-related disease and mostly diagnosed after the sixth decade of life, though it may also be diagnosed earlier. Objective. The aim of this study is to explore the clinicopathological characteristics and prognosis of gastric carcinoma in young patients. Methods. A total of 1379 patients younger than 75 years histologically diagnosed with primary gastric carcinoma underwent gastrectomy. Patients were categorized into three groups based on their age which included young age group (≤40 years), middle-aged group (age 41-60 years), and elderly group (age 61-75 years). The young age group was further subdivided into two groups: Group A (age ≤35 years) and Group B (age 35-40 years). The analysis of the clinicopathological characteristics and prognosis followed thereafter. Results. Females predominate in young group (p<0.001). A significantly higher undifferentiated histological pattern was found in the young age group from the other two groups (p<0.001). Tumor location in the lower third of the stomach was significantly higher in the young group than the other groups (p<0.001). T4 stage was common in young patients similar to the middle and old age group (p=0.049). Distal gastrectomy was performed more in the young age group rather than the middle and old age groups with the following percentage ratios: young group 74.5% (123/165), middle age group 59.9% (429/716), and old age group 52.2% (260/498) (p<0.001). The 5-year overall survival rate of the young, middle, and old age groups were 46%, 48%, and 39%, respectively, whereas the 5-year overall survival rates of the subgroups of young patients, Group A and Group B, were 33% and 49%, respectively. Multivariate analysis revealed that independent negative prognostic factors were as follows: tumor location (L), p=0.016, OR=0.795, 95%CI=0.659;0.959; larger tumor size, p=0.026, OR=1.727, 95%CI=1.067;2.797; resection margin, p<0.001, OR=2.167, 95%CI=1.751;2.682; tumor stage (T4), p<0.001, OR=2.572, 95%CI=1.709;3.870; and nodal involvement N1, p=0.005, OR=1.506, 95%CI=1.123;2.020; N2, p<0.001, OR=1.708, 95%CI=1.289;2.263; and N3, p<0.001, OR=2.986, 95%CI=2.314;3.854. Conclusion. The young age groups of patients were predominantly female and had a higher proportion of poorly differentiated and undifferentiated type of tumor; moreover, patients aged <35 years had a poor prognosis. In addition, gastric cancer can occur in patients less than 30 years old, and symptoms suggestive of gastric cancer should be investigated aggressively; therefore, a close scrutiny and monitoring should be done in younger patients especially those associated with high-risk factors which could indicate the presence of the disease at an early stage.